PENGARUH KONTRIBUSI, SIKAP DAN KESADARAN WAJIB PAJAK TERHADAP TINGKAT KEPATUHAN DALAM MEMBAYAR PBB DI KABUPATEN SUKOHARJO - Nursiam Nursiam; Ila Marliana Purnama (STKIP NU Kabupaten Tegal, 2022)
This study aims to determine and analyze the effect of taxpayer contributions, taxpayer attitudes and taxpayer awareness on the level of compliance in paying Land and Building Tax in Sukoharjo Regency. The population used in this study is land and building tax taxpayers registered with the BKD Sukoharjo Regency. The number of samples used in this study were 100 respondents who were calculated based on theformula Slovin with the sample method used was Conveniance Sampling. The type of data used in this study is primary data obtained through questionnaires. Hypothesis testing in this study uses multiple linear regression analysis using the SPSS version 20 program. The results of this study indicate that the taxpayer contribution variable has no significant effect on taxpayer compliance, the taxpayer's attitude has no effect on taxpayer compliance, while the taxpayer awareness variable has a significant effect. to taxpayer compliance.